Effects of Ferric Chloride as Secondary Dopant on the Properties of Polyethylene Oxide / Polyvinyl Chloride / Polyaniline Conductive Films - Mohd Yazid, Mohammed Izzuddeen; Yusof, Norliana; Osman, Azlin Fazlina; Pargi, Mohamad Nur Fuadi; Faris, Meor Ahmad; Nainggolan, Irwana (Journal of Advanced Research Design, 2025)
Polyethylene oxide (PEO) / Polyvinyl chloride (PVC) blends with 2.5 wt% - 10 wt% polyaniline (PAni) loadings were fabricated with and without the presence of ferric chloride (FeCl3). PEO/PVC/PAni and PEO/PVC/PAni-FeCl3 conductive films were prepared by solution casting method using tetrahydrofuran as the solvent at ambient temperature. The electrical conductivity of the conductive films was analyzed and discussed in this paper. The study found that higher loading of PAni increased the electrical conductivity of the films and further improved with the addition of FeCl3. The XRD analysis study supported the findings by revealing the modified structure of PAni, with FeCl3 as the oxidizing agent. The tensile strength, however, decreased with the addition of PAni and FeCl3 in the conductive films due to poor agglomeration of filler.